PENGARUH LATIHAN TEKNIK RENANG GAYA BEBAS MENGGUNAKAN PAPAN PELAMPUNG PADA ANAK USIA 7-14 TAHUN DI CLUB RENANG GLODIUS SWIMM - James Riady Ketaren; Deasyi Natalia Sitepu (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of freestyle swimming technique training using a kickboard on improving freestyle swimming skills among children aged 7–14 years at Glodius Swim Swimming Club. This research employed a quantitative method with an experimental approach using a One Group Pretest–Posttest Design. The population of this study consisted of swimming training participants at Glodius Swim Swimming Club aged 7–14 years, with a sample of 10 children selected through a purposive sampling technique. The research instruments were observation sheets and freestyle swimming skill assessment rubrics covering body position, kicking technique, arm stroke, breathing coordination, and overall freestyle movement coordination. Data collection was conducted through an initial test ( pretest ) before the treatment and a final test ( posttest ) after participants received freestyle swimming technique training using a kickboard. Data analysis was carried out through prerequisite tests, including normality and homogeneity tests, followed by hypothesis testing using the Paired Sample t-test to determine differences between pretest and posttest results. The results showed that freestyle swimming technique training using a kickboard improved freestyle swimming skills among children aged 7–14 years at Glodius Swim Swimming Club. The use of a kickboard helped participants maintain body position, improve coordination between leg and arm movements, and develop better breathing techniques, resulting in more effective freestyle swimming performance.